Relationship Between Waist Circumference with HS-CRP (High Sensitivity C-Reactive Protein) Levels in Men - Ayudhawati, Reynindra Cakra; Saktiningsih, Hari (Jurnal Biologi Tropis, 2025)
High-sensitivity C-reactive protein (hs-CRP) levels are inflammatory markers that can be influenced by visceral adipose tissue, especially since sex hormones also influence fat storage patterns and the incidence of central obesity. This study examined the relationship between waist circumference and hs-CRP levels in men. This study used an analytical observational study type with a cross-sectional approach. Statistical analysis of 24 samples using the non-parametric Rank-Spearman test obtained a significance value (p < 0.05); r = 0.763. This study shows a significant relationship between men's waist circumference and Hs-CRP levels. Further research can pay attention to variables that can increase Hs-CRP levels, such as physical activity, food intake, other infectious diseases, and examination of blood glucose, cholesterol, and blood pressure levels.